Perbandingan Metode Depth of Field pada Lensa Kamera Fotografi dengan Efek Lensa pada Software Animasi - Ahmad Faisal Choiril Anam Fathoni; Dermawan Syamsuddin (Bina Nusantara University, 2013)
The knowledge of photography becomes fundamental importance in the understanding of digital cinematography. The work of a good photography is a blend of knowledge and photographic ability (skill) correctly. By learning photography properly, it allows an animator or digital art workers to apply some standard cinematography as well. By knowing the comparison between photography with